Optimization of (131)I doses for the treatment of hyperthyroidism - Araujo, F.; Rebelo, A. M. O.; Rebelo, A. M. O.; Pereira, A. C.; Moura, M. B.; Lucena, E. A.; Dantas, A. L. A.; Dantas, B. M.; Corbo, R. (Cellular and Molecular Biology, 2009)
Several methods can be used to determine the activity of 131I in the treatment of hyperthyroidism. However, many of them do not consider all the parameters necessary for optimum dose calculation. The relationship between the dose absorbed by the thyroid and the activity administered depends basically on three parameters: organ mass, iodine uptake and effective half-life of iodine in the thyroid. Such parameters should be individually determined for each patient in order to optimize the administered activity. The objective of this work is to develop a methodology for individualized treatment with 131I in patients with hyperthyroidism of the Grave’s Disease. A neck-thyroid phantom developed at the IRD was used to calibrate a scintillation camera and a uptake probe SCT-13004 at the Nuclear Medicine Center of the University Hospital of Rio de Janeiro and a uptake probe SCT-13002, available at the Nuclear Medicine Institute in Goií¢nia. The biokinetic parameters were determined based on measurements performed in eight voluntary patients. It is concluded that the use of the equipment available at the hospital (scintillation camera and uptake probe) has shown to be a suitable and feasible procedure for dose optimization in terms of effectiveness, simplicity and cost.